Strategi Penguatan Pendidikan Karakter Siswa di SMK PGRI Wlingi, Kabupaten Blitar - Darmaningtyas, Novia Ardhana; Rapita, Desinta Dwi (Journal of Moral and Civic Education, 2024)
Character education is important for vocational school students. This is because students' character is currently experiencing a decline, so appropriate strategies are needed to strengthen character education in schools. The aim of this study is to discuss strategies for strengthening character education in vocational schools. A qualitative approach with descriptive research was used in this study. Interactive data analysis with data collection techniques through observation, interviews and documentation. The results of the study show that the strategies used by PGRI Wlingi Vocational School can be carried out through state defense activities and through habituation of activities at school. All new students must participate in national defense activities and collaborate with the Indonesian National Army. The habituation carried out is the internalization of character values ​​in the curriculum through Learning Implementation Plans and learning media, intracurricular and extracurricular activities. The internalized values ​​are religious values, integrity, independence, mutual cooperation and nationalism.